Pendampingan Sertifikasi Halal Untuk Meningkatkan Kualitas UMKM di Desa Bulu Kecamatan Purwoasri Kabupaten Kediri - Pramadani, Krisna Ayuda; Kusumaningrum, Dian Moulina; Fitriani, Fitriani; Puspitasari, Eva Setyarini; Virginita, Fathin Ilma; Arzaq, Falik Izza Haidar; Silviana, Ika (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Halal Product Guarantee Administering Agency (BPJPH), in accordance with Law no. 33 of 2014, regulates the Halal Certification process in Indonesia, including the Free Halal Certification (Self Declare) program for MSMEs. Community service in Bulu Village, Purwoasri District, Kediri Regency, focuses on assisting MSMEs in the Free Halal Certification process. This activity aims to ensure that MSME products meet halal standards, improve quality and product competitiveness. Using the Participatory Action Research (PAR) method, this activity actively involves MSMEs, BPJPH, and local communities to support the administrative certification process while strengthening business actors' understanding of the importance of halal products. As a result, this program not only helps MSMEs obtain halal certification but also provides long-term positive impacts in the form of increasing the capacity of business actors and product competitiveness in the global market. This assistance contributes to the creation of a more inclusive and sustainable local economy.